2021
DOI: 10.3389/fpls.2021.628294
|View full text |Cite
|
Sign up to set email alerts
|

Planting Density Affects Panax notoginseng Growth and Ginsenoside Accumulation by Balancing Primary and Secondary Metabolism

Abstract: Adjusting planting density is a common agricultural practice used to achieve maximum yields. However, whether the quality of medicinal herbs can be improved by implementing appropriate planting densities is still uncertain. The medicinal crop Panax notoginseng was used to analyze the effects of planting density on growth and ginsenoside accumulation, and the possible mechanisms of these effects were revealed through metabonomics. The results showed that P. notoginseng achieved high ginsenoside accumulation at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 61 publications
(73 reference statements)
0
15
0
Order By: Relevance
“…A key goal in commercialized plant production is to optimize growth and the biosynthesis of desirable secondary metabolites. However, environmental factors, and agricultural practices can strongly impact theses outcomes [ 53 , 54 ]. Among these, planting density is the most effective factor influencing plant growth and crop quality [ 15 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A key goal in commercialized plant production is to optimize growth and the biosynthesis of desirable secondary metabolites. However, environmental factors, and agricultural practices can strongly impact theses outcomes [ 53 , 54 ]. Among these, planting density is the most effective factor influencing plant growth and crop quality [ 15 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Andrographolide (AP1), the major secondary metabolite in Andrographis, has numerous pharmacological effects [ 66 68 ]. Findings in Liu [ 54 ] and Verma [ 60 ] found that the synthesis of secondary metabolites in Panax notoginseng and Andrographis paniculata were enhanced when growing at high densities. Although the accumulation of AP1 content in mg g -1 DW -1 is not affected by planting density across developmental stages ( S2 Table ), when AP1 content was expressed as mg DW -1 m -2 , the production of AP1 content was significantly higher at 30 plants per m 2 compared with other planting densities ( Fig 6 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All these initial reactions involve synthesizing and degrading amino acids to produce primary metabolites such as carbohydrates, proteins, and lipids (Singh et al, 2020). The primary metabolism provides the necessary energy and precursor substances for the biosynthesis of secondary metabolites in the final step (Liu et al, 2017;Liu et al, 2021).…”
Section: Correlation Of Economic Traits With Functional Traits Of Ble...mentioning
confidence: 99%
“…The content of active ingredients is considered the key to determining MPs’ clinical efficacy. Among them, secondary metabolites are the main substances with pharmacodynamic functions [ 290 , 291 ]. Chen et al [ 246 ] demonstrated that rhizosphere microbiota was closely related to the contents of oxymatrine, sophoridine and matrine in Sophora flavescens roots.…”
Section: Function Of Soil Microorganisms In Growth Promotion and Qual...mentioning
confidence: 99%